Cyborg-Technology Relations - Shew, Ashley; Earle, Joshua (Journal of Human-Technology Relations, 2024)
We advocate for a philosophizing of cyborg-technology relations that takes account disabled technology users. First, we sketch out how tech-driven ableism (“technoableism”) is present in most discourse about technology, and then address how ableism has shaped accounts of disability in philosophy more broadly too. We examine this in historical and media context, then turn to what an unapologetic disability-forward approach to cyborg-technology relations looks like, and what it means to listen to the cyborgs we know and love. This work draws from the interdisciplinary field of disability studies and STS work on crip technoscience. We situate this work mostly within North American media and history of disability and Silicon Valley boosterism on tech, but accounts of technology and of disability are not unique to these locations.